Prospects of China-EAEU Cooperation on Digital Economy - N. V. Yurova; Yao Jiahui (Цифровая трансформация, 2019)
The purpose of the article is to identify prospects of cooperation on digital economy between China and the EAEU member states in the framework of the Conjunction of the EAEU and the “One Belt, One Road” initiative. The article shows that the digital economy as a result of the genesis of the information revolutions is a new key engine for sustainable economic development, improvement of productivity, reconfiguration of the international division of labor and the deepening of globalization processes and the emergence of new markets and industries in the world in the post-crisis period. The article reveals the characteristic of the development of digital economy in the World and analyzes the development of digital economy in China and the EAEU member states. Based on revealing the main idea of China's Digital Silk Road and the essence of the EAEU Digital Agenda, the main promising directions for the development of cooperation between China and the EAEU in the framework of the “One Belt, One Road” initiative were identified: improve information and communication technology (ICT) infrastructure and facilitate Cross-Border Data Flows; expand the scope of cooperation and sign trade facilitation agreements at Union level and at the national level; move to a new level of mutually beneficial cooperation on digital economy of the China-EAEU-EU.